2020
DOI: 10.1126/sciadv.aaz4848
|View full text |Cite
|
Sign up to set email alerts
|

Attenuated diphtheria toxin mediates siRNA delivery

Abstract: Toxins efficiently deliver cargo to cells by binding to cell surface ligands, initiating endocytosis, and escaping the endolysosomal pathway into the cytoplasm. We took advantage of this delivery pathway by conjugating an attenuated diphtheria toxin to siRNA, thereby achieving gene downregulation in patient-derived glioblastoma cells. We delivered siRNA against integrin-β1 (ITGB1)—a gene that promotes invasion and metastasis—and siRNA against eukaryotic translation initiation factor 3 subunit b (eIF-3b)—a surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 49 publications
(54 reference statements)
1
22
0
Order By: Relevance
“…Utilizing bacterial toxin-based systems to deliver cargoes into the cytosol of cells has been explored with various toxins such as DT ( Arnold et al, 2020 ; Auger et al, 2015 ; Vidimar et al, 2020 ), BoNTs ( Bade et al, 2004 ; McNutt et al, 2021 ; Miyashita et al, 2021 ), anthrax toxin ( Milne et al, 1995 ; Young and Collier, 2007 ), Pseudomonas exotoxin A ( Ryou et al, 2016 ; Verdurmen et al, 2015 ), heat-labile enterotoxin ( Chen et al, 2015 ), Shiga toxins ( Ryou et al, 2016 ; Schmit et al, 2019 ), Clostridium botulinum C2 toxin ( Barth et al, 2002 ; Fahrer et al, 2013 ), and Photorhabdus luminescens Tc toxins ( Ng Ang et al, 2019 ; Roderer et al, 2019 ). The mechanisms of membrane translocation differ among these toxins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing bacterial toxin-based systems to deliver cargoes into the cytosol of cells has been explored with various toxins such as DT ( Arnold et al, 2020 ; Auger et al, 2015 ; Vidimar et al, 2020 ), BoNTs ( Bade et al, 2004 ; McNutt et al, 2021 ; Miyashita et al, 2021 ), anthrax toxin ( Milne et al, 1995 ; Young and Collier, 2007 ), Pseudomonas exotoxin A ( Ryou et al, 2016 ; Verdurmen et al, 2015 ), heat-labile enterotoxin ( Chen et al, 2015 ), Shiga toxins ( Ryou et al, 2016 ; Schmit et al, 2019 ), Clostridium botulinum C2 toxin ( Barth et al, 2002 ; Fahrer et al, 2013 ), and Photorhabdus luminescens Tc toxins ( Ng Ang et al, 2019 ; Roderer et al, 2019 ). The mechanisms of membrane translocation differ among these toxins.…”
Section: Discussionmentioning
confidence: 99%
“…This is possibly because the RNA components dissociate from Cas proteins during membrane translocation; there-fore, the crRNA components must be co-delivered by other methods. A recent study showed that a DT-based system can be used to deliver siRNA into cells ( Arnold et al, 2020 ), suggesting that crRNA may be delivered using AB toxin-based systems.…”
Section: Discussionmentioning
confidence: 99%
“…However, in its current state, the CRISPA approach needs to be combined with other viral or non-viral methods that are capable of delivering the single guide RNA into cells. Notably, a transient toxin-based siRNA delivery strategy was developed just recently on the basis of an attenuated diphtheria toxin ( Arnold et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…First, they conjugated DT with cysteine (Cys); next, the Cys was modified with a maleimide cross-linked to dibenzocyclooctyne (DBCO) group and the siRNA molecules were attached to the DBCO. When the conjugated DT was added to GSCs, significant reductions in the mRNA levels of ITGB1 and eIF-3b were observed ( 127 ). More studies using bacterial toxins for RNAi delivery should be performed in GBM cells and GBM mouse models.…”
Section: Delivery Strategies For Rnai-based Therapies Against Gbmmentioning
confidence: 99%